Case Report: The First Report on Moraxella canis Isolation From Corneal Ulcer in a Bulldog - Wang, Zhihao; Guo, Long; Li, Jun; Li, Jianji; Cui, Luying; Dong, Junsheng; Wang, Heng (Frontiers in Veterinary Science, 2022)
A 5-year-old castrated male bulldog was diagnosed with a corneal ulcer accompanied by edema and conjunctival hyperemia. Ophthalmic examination and microbiological analysis were performed, and the bacteria were found to be gram-negative and globular. The isolated clone was identified as Moraxella canis (MZ579539) via MALDI-TOF MS and 16S rDNA sequencing. Antimicrobial susceptibility testing showed that the bacteria were sensitive to tetracycline and chloramphenicol, but resistant to levofloxacin and ciprofloxacin. After a conjunctival flap was placed, tobramycin ophthalmic solution and 5% sodium hyaluronate were administered. Following surgery, the ulcer was effectively controlled, and after 3 weeks, the cornea healed. This is the first case report of a canine corneal ulcer associated with M. canis, which should be considered when corneal ulceration or keratitis were suspected.